Analysis of the research “Social imaginaries of human development, underlying the policies of resocialization of internal professional women, in the Villa Cristina Penitentiary Center in the city of Armenia, Quindío, Colombia”: conducted by Quinceno, J; Morales, L & Cuellar, L, 2015. (Revista de Investigaciones Universidad del Quindío, 2021)
This paper is a letter to the editor, in which an analysis of the research carried out by Quiceno, J; Morales, L & Cuellar, L (2015) is made, called “Social Imaginaries of Human Development, underlying in the Policies of Resocialization of Internal Professional Women, at Villa Cristina Penitentiary, in the city of Armenia, Quindío, Colombia. This is a qualitative research from the phenomenological method, used techniques for the collection of information such as the interview and the focus group; female prisoners who are professionals participated, so the sampling is non-probabilistic of convenience. The data were analyzed in coherence with the phenomenological method, concluding that the resocialization policies applied in this female prison center do not achieve their objective, nor are they used properly, therefore, the authors propose the design of a public policy of differential resocialization.The criteria used to evaluate this research were: study purposes, literature review, study design, sampling, data collection, data analysis, general rigor, conclusions, and significance. Based on the above, it can be affirmed that the research by Quiceno et al. (2015) meets all the criteria that show the theoretical and methodological rigor used, therefore, it has validity and reliability.
Keywords: social imaginary; human development; resocialization policies; prison system